Evaluasi Program Ekstrakurikuler Keagamaan di Sekolah - Baqi Nurul Hakkurahmy (Arus Jurnal Pendidikan, 2023)
Islamic Religious Education is one of the subjects that must be taught at all types and levels of education in Indonesia. The strategic position of these subjects is related to efforts to achieve national education goals, namely the formation of human beings who believe and fear God Almighty. This type of research is descriptive research. The approach used in this study is a qualitative approach. The qualitative approach in this study was used to describe the evaluation of the Islamic Religious Education program at the Cordova Samarinda Integrated Islamic Elementary School. The results of the research and data processing are: 1) Evaluation procedures for religious extracurricular programs covering three aspects, namely cognitive, affective and psychomotor aspects have been carried out. 2) Implementation of religious extracurricular evaluations, at SDIT Cordova it is held in formal hours because learning is carried out from morning to evening as for adding practice hours it is carried out on Saturdays and Sundays. 3) Follow-up on the evaluation of religious extracurricular programs, at SDIT Cordova it is used to develop school programs, take part in competitions, report data to students' parents and provide material for consideration for continuing to high school and leading activities at school.